2021
DOI: 10.3390/ijms222413358
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin Signaling in Cancer and Autoimmune Diseases

Abstract: Cadherins mediate cell–cell adhesion through a dynamic process that is strongly dependent on the cellular context and signaling. Cadherin regulation reflects the interplay between fundamental cellular processes, including morphogenesis, proliferation, programmed cell death, surface organization of receptors, cytoskeletal organization, and cell trafficking. The variety of molecular mechanisms and cellular functions regulated by cadherins suggests that we have only scratched the surface in terms of clarifying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 175 publications
1
17
0
Order By: Relevance
“…In our study, the functional annotation of FLVCR2 revealed that cell–cell adhesion, cellular defense response, translational initiation, and ribonucleoprotein complex biogenesis were closely associated with FLVCR2 expression. Studies have shown that adhesion molecules are closely related to tumorigenesis and development ( Sisto et al, 2021 ; Ito et al, 2022 ), which is consistent with our results. The cell–cell adhesion events enriched in the high FLVCR2 expression group show that FLVCR2 plays a critical role in AML tumorigenesis.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the functional annotation of FLVCR2 revealed that cell–cell adhesion, cellular defense response, translational initiation, and ribonucleoprotein complex biogenesis were closely associated with FLVCR2 expression. Studies have shown that adhesion molecules are closely related to tumorigenesis and development ( Sisto et al, 2021 ; Ito et al, 2022 ), which is consistent with our results. The cell–cell adhesion events enriched in the high FLVCR2 expression group show that FLVCR2 plays a critical role in AML tumorigenesis.…”
Section: Discussionsupporting
confidence: 93%
“…The TAZ knockdown experiment suggested that TAZ may serve an important role in the process of ADSCs delaying the progression of SS. In addition, it has been previously noted that the expression of E-cadherin will change with the progression of autoimmune diseases ( 26 , 27 ). The reason for these phenomena may be the different pathogenesis of the different autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is now widely unquestioned that the development of a fibrotic program in SS is due to the production of fibrogenic mediators by inflammatory and epithelial cells; among these mediators, a main role is played by the growth factor TGF-β1 [ 76 ]. Pioneering studies conducted by Sisto and colleagues demonstrated that TGF-β1 promotes an SG epithelial cell transition toward the mesenchymal phenotype through the activation of EMT-dependent fibrosis [ 75 , 77 , 78 ]. Experimental in vitro studies performed on human SG epithelial cells have shown that TGF-β1 induces the transition of SG epithelial cells from the classic cobblestone morphology toward a more spindle-shaped fibroblast cell type characterized by a reduction in the expression level of epithelial adherence junction proteins [ 75 , 77 , 78 ].…”
Section: New Insights Into the Regulation Of Epithelial–mesenchymal T...mentioning
confidence: 99%
“…Pioneering studies conducted by Sisto and colleagues demonstrated that TGF-β1 promotes an SG epithelial cell transition toward the mesenchymal phenotype through the activation of EMT-dependent fibrosis [ 75 , 77 , 78 ]. Experimental in vitro studies performed on human SG epithelial cells have shown that TGF-β1 induces the transition of SG epithelial cells from the classic cobblestone morphology toward a more spindle-shaped fibroblast cell type characterized by a reduction in the expression level of epithelial adherence junction proteins [ 75 , 77 , 78 ]. This was supported by the observation that SG biopsies derived from pSS patients show an elevated expression of TGF-β1 [ 77 , 78 ].…”
Section: New Insights Into the Regulation Of Epithelial–mesenchymal T...mentioning
confidence: 99%
See 1 more Smart Citation